Association of quantitative interferon‐γ responses with the progression of naturally acquired Mycobacterium bovis infection in wild European badgers (Meles meles). Issue 2 (February 2015) - Tomlinson, Alexandra J.; Chambers, Mark A.; McDonald, Robbie A.; Delahay, Richard J.
Summary Bovine tuberculosis is one of the biggest challenges facing cattle farming in Great Britain. European badgers (Meles meles) are a reservoir host for the causal agent, Mycobacterium bovis. There have been significant recent advances in diagnostic testing for tuberculosis in humans, cattle and badgers, with the development of species‐specific assays for interferon‐γ (IFN‐γ), an important cytokine in tuberculous infections. Using data collected from longitudinal studies of naturally infected wild badgers, we report that the magnitude of the IFN‐γ response to M. bovis antigens at the disclosing test event was positively correlated with subsequent progression of disease to a seropositive or excreting state. In addition, we show that the magnitude of the IFN‐γ response, despite fluctuation, declined with time after the disclosing event for all badgers, but remained significantly higher in those animals with evidence of disease progression. We discuss how our findings may be related to the immunopathogenesis of natural M. bovis infection in badgers.